Colorimetric detection of uric acid in human urine and serum based on peroxidase mimetic activity of MIL-53(Fe). Issue 23 (5th November 2015) - Lu, Junyu; Xiong, Yuhao; Liao, Chunjin; Ye, Fanggui
Abstract : The porous metal–organic framework MIL-53(Fe) was prepared using a simple solvothermal method, and was developed as a colorimetric sensor for the detection of uric acid in human urine and serum. Abstract : The porous metal–organic framework MIL-53(Fe) was prepared using a simple solvothermal method, using FeCl3 ·6H2 O and 1, 4-benzenedicarboxylic acid as the precursor, and characterized by X-ray diffractometry, Fourier transform infrared spectroscopy and scanning electron microscopy. The MIL-53(Fe) was demonstrated to possess an intrinsic peroxidase-like activity, and it could catalyze the oxidation of the peroxidase substrate 3, 3′, 5, 5′-tetramethylbenzidine into a blue colored product in the presence of H2 O2 . Based on this phenomenon, MIL-53(Fe) was developed as a colorimetric sensor for the detection of uric acid (UA) in human urine and serum. This provided a simple and effective method for UA detection using uricase and MIL-53(Fe), with a linear range from 4.5 to 60 μM, and a detection limit of 1.3 μM (S/N = 3). Moreover, the proposed method can be successfully applied to the determination of UA in human urine and serum samples with recoveries and relative standard deviations between 1.2–4.8% and 89.50–101.44%, respectively.